DESIGN AND BUILD A MICROCONTROLLER BASED DIP COATER TOOL WITH AN AUTOMATIC CALIBRATION SYSTEM - Rahman, Nizar Rizki; Sya’roni, Imam; Hartanto, Anton; Prasetyono, Agus Dwi; Subiantoro, Irfan (Indonesian Physical Review, 2025)
Dip-coating is essential for coating materials evenly, as imperfections like macropores can impact material properties. This project presents a digitally controlled dip-coating tool that manages withdrawal speed, immersion time, and speed via a microcontroller with an automatic calibration system. Employing a stepper motor and mathematical formula approach, the tool achieves high precision by automatically adjusting dipping parameters, with key metrics including resolution-dependent Vl, calibration speed Vpc and calibration targets tpc, and Sc. The system reaches stable calibration at Vms = Vpc. ensuring rapid, accurate calibration and minimizing errors to 0-2% across 20 to 650 steps. Additionally, the tool’s energy-efficient design consumes less power than other dip-coating systems, providing both durability and accuracy.